Flexible C–Mo2C fiber film with self-fused junctions as a long cyclability anode material for sodium-ion battery. Issue 30 (8th May 2018) - Zhang, Wenjie; Guo, Zeyu; Liang, Qinghua; Lv, Ruitao; Shen, Wanci; Kang, Feiyu; Weng, Yuqing; Huang, Zheng-Hong
Abstract : Fiber junctions were fused by introducing MoO2, that eliminates the contact resistance at fiber junctions, and significantly improves the cyclability. Abstract : Electrospun carbon fiber films have high contact resistance at the fiber junctions, which causes poor cycling stability and limits their further improvement in energy storage performances. To eliminate the contact resistance of the film, we provide a new strategy to fuse the fiber junctions by introducing MoO2 in the fibers, which replaces the C–C interface by a more active C–MoO2 –C interface at the fiber junction to promote mass transfer. MoO2 reacts with C matrix to generate Mo2 C and form self-fused junctions during the carbonization process. Due to much lower charge transfer and sodium diffusion resistance, the C–Mo2 C fiber film with self-fused junctions shows much better cyclability with capacity retention of 90% after 2000 cycles at a constant current density of 1 A g −1 . Moreover, the Mo2 C particles provide many electrochemically active sites, leading to additional improvement in sodium storage. The C–Mo2 C fiber film has a capacity of 134 mA h g −1 at 1 A g −1 and a high capacity of 99 mA h g −1 even at 5 A g −1 .